(untitled) (Trabalho & Educação, 2016)
This study aimed to define the socioeconomic and productive profile of the land crab pickers in the city of Quatipuru, Pará. The data were obtained through field visits and questionnaires, and sampling was non-probabilistic.As for the results, it was found that the crab pickers in the city of Quatipuru - PA, are mostly female, graduating elementary school, adults with home ownership and average household income / month 87 reais, arising from the processing activity, and complement the Bolsa Familia program. With this, the crab pickers studied require the government’s role in generating social and environmental actions in order to maintain the activity and preservation of biological resources, generation of employment, income and improve the population’s quality of life . ___ O presente estudo teve como objetivo definir o perfil socioeconômico e produtivo dos catadores de caranguejo-uçá do município de Quatipuru, Pará. Os dados foram obtidos através de visitas a campo e aplicação de questionários, e a amostragem foi não probabilística. Quanto aos resultados, constatou-se que os catadores de caranguejo do município de Quatipuru – PA, são em sua maioria do sexo feminino, concluintes do ensino fundamental, adultos, com casa própria e renda familiar média/mês de 87 reais, advinda da atividade de beneficiamento, e da complementação do programa Bolsa Família. Com isso, os catadores de caranguejo estudados necessitam da atuação do poder público na geração de ações socioambientais a fim de manter a atividade e preservação dos recursos biológicos, geração de emprego, renda e melhoria da qualidade de vida da população.